2014
DOI: 10.3109/09513590.2014.916263
|View full text |Cite
|
Sign up to set email alerts
|

Follicular progesterone elevations with ovulation induction for IVF

Abstract: The purpose of this review is to analyse the sources and effects of follicular progesterone elevations during ovarian stimulation, with the underlying mechanisms and preventive strategies on the in vitro fertilisation pregnancy outcome. In the early follicular phase, a flare-up effect of gonadotrophin releasing hormone (GnRH) agonists and incomplete luteolysis in GnRH antagonist regimens can result in significant elevations of progesterone. In the late follicular phase, progesterone elevations in GnRH analogue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In addition, we also found that progesterone rises rapidly just before and after HCG administration, and increased by about five-fold over a 24-h period. The mechanism of P elevation on the day of HCG administration and the relationship to the LH activity has been addressed in a recent review, which suggested that premature luteinization is a misnomer and that the elevated progesterone is direct consequence of FSH stimulation and multiple follicle development (Kasum et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also found that progesterone rises rapidly just before and after HCG administration, and increased by about five-fold over a 24-h period. The mechanism of P elevation on the day of HCG administration and the relationship to the LH activity has been addressed in a recent review, which suggested that premature luteinization is a misnomer and that the elevated progesterone is direct consequence of FSH stimulation and multiple follicle development (Kasum et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that progesterone produced in IVF/ICSI is related to the number of follicles ( 23 , 24 ). In this study, we hypothesised that late elevations in follicular blood progesterone might be owing to the following reasons: 1) An increase in progesterone secretion from the recruited follicles; the greater the number of follicles, the higher the progesterone level, which could be induced by any protocol; 2) pathological progestogen, which is related to the premature luteinisation of follicles and decreased follicle quality.…”
Section: Discussionmentioning
confidence: 99%
“…In the late follicular phase, progesterone elevations in GnRH analog cycles are the result of the ovarian stimulation itself, driven by high follicle stimulating hormone dosage, estradiol levels, and the numbers of follicles and oocytes. It seems that progesterone elevations (C 1.5 ng/mL or 4.77 nmol/L) have a detrimental effect on the outcome of pregnancy, accelerating the endometrial maturation [32,33]. The most appropriate choice to avoid the negative effects of follicular progesterone elevations is to cancel fresh embryo transfer and to transfer frozen-thawed embryos in natural cycles.…”
Section: Discussionmentioning
confidence: 99%
“…The most appropriate choice to avoid the negative effects of follicular progesterone elevations is to cancel fresh embryo transfer and to transfer frozen-thawed embryos in natural cycles. To prevent follicular-phase elevations, it might be preferable to use milder stimulation protocols, earlier trigger of ovulation in high responders, and single-blastocyst transfer on day 5 [32]. The optimal GnRH analog protocols during the entire stimulation period appear to be the long agonist as well as ''long'' and long GnRH antagonist regimens [33].…”
Section: Discussionmentioning
confidence: 99%